2022
DOI: 10.4143/crt.2021.131
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cancer Patient Decision-Making and Health Service Utilization after Enforcement of the Life-Sustaining Treatment Decision-Making Act in Korea

Abstract: This study aimed to confirm the decision-making patterns for life-sustaining treatment and analyze medical service utilization changes after enforcement of the Life-Sustaining Treatment Decision-Making Act. Materials and MethodsOf 1,237 patients who completed legal forms for life-sustaining treatment (hereafter called the life-sustaining treatment [LST] form) at three academic hospitals and died at the same institutions, 1,018 cancer patients were included. Medical service utilization and costs were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Even after the implementation of the life-sustaining-treatment act, there have been cases where patients who had written an advance directive were admitted to the intensive care unit and received a similar level of intervention as patients without an advance directive. In Korea, ICU hospitalization and invasive interventions often occur against the patient’s wishes, especially if the family is unaware of or does not agree with the patient’s wishes regarding end-of-life care [ 33 ]. Therefore, it is important for healthcare providers to discuss POLST with both patients and families prior to ICU admission to clarify the meaning and scope of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even after the implementation of the life-sustaining-treatment act, there have been cases where patients who had written an advance directive were admitted to the intensive care unit and received a similar level of intervention as patients without an advance directive. In Korea, ICU hospitalization and invasive interventions often occur against the patient’s wishes, especially if the family is unaware of or does not agree with the patient’s wishes regarding end-of-life care [ 33 ]. Therefore, it is important for healthcare providers to discuss POLST with both patients and families prior to ICU admission to clarify the meaning and scope of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…With the estimation of EoL patients that followed the process required by the Act only as 20–25%, 9 several studies found that the use of intensive care unit hospitalization, ventilator, and cardiopulmonary resuscitation did not differ after legalization, suggesting that this restriction may lead to potential delays in avoiding LST. 19 20 21 It may be an excessive violation of the rights of EoL patients who have not been judged as being actively dying despite the burden of treatment and goal of care at the terminal phase are not significantly different compared to the dying phase. Moreover, when a patient has a non-cancerous condition, such as organ failure or dementia, these limitations are more pronounced, as distinguishing the dying phase from the terminal phase is challenging.…”
Section: Restriction Of the Right To Refuse Unwanted And Burdensome T...mentioning
confidence: 99%
“…As the system gains usage experience, the characteristics of collected PROs need analysis, including adjustments to the number of monitored symptoms (and variables) and alleviate chemotherapy-related anxiety [19], whereas Smart Cancer Care 2.0, addressing all aspects of cancer treatment, is expected to enhance patients' learning and self-efficacy. This could facilitate the adoption of shared decision-making in the broader field of cancer treatment [25,26]. From healthcare workers' perspectives, Smart Cancer Care 2.0 is anticipated to aid in forming a rapport with patients and providing personalized treatment, as evidenced by the feasibility evaluation score, which is higher than that of patients.…”
Section: Cancer Research and Treatment (Crt) 12mentioning
confidence: 99%